2005
DOI: 10.1021/ja042152q
|View full text |Cite
|
Sign up to set email alerts
|

Alkane Coordination Selectivity in Hydrocarbon Activation by [Tp‘Rh(CNneopentyl)]:  The Role of Alkane Complexes

Abstract: The competitive activation of C-H bonds of linear, cyclic, and branched hydrocarbons using the coordinatively unsaturated 16-electron [Tp'RhL] reactive fragment have been studied (Tp' = tris-(3,5-dimethylpyrazolyl)borate; L = CNCH2CMe3). Activation of the hydrocarbons leads to the formation of Tp'Rh(L)(R)(H) alkyl complexes, which were converted to the stable chlorides immediately following the activation of the bonds via photolysis of Tp'Rh(L)(PhN=C=NCH2CMe3) in the solvent mixture. The products were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 35 publications
6
52
0
1
Order By: Relevance
“…The extensive isotopic scrambling observed for the reaction of 2-d 0.43 with C 6 D 12 , giving CH 2 D 2 and CHD 3 (CD 4 is presumably also formed, but not detected by 1 H NMR) in addition to the CH 3 D, and CH 4 obtained from reactions of all-protio substrates, indicates that reversible steps iii and iv along with COH bond interchange in cyclohexane and methane COH complexes (see below) are all fast relative to loss of methane, consistent with rate-determining COH coordination. This conclusion is further supported by the small KIE [(k H /k D ϭ 1.28(5)], which is similar to values measured for iridium-and rhodium-based COH activation systems where COH coordination is rate-determining (k H /k D Ϸ 1.1-1.4) (22-24), but considerably smaller than values for rate-determining oxidative cleavage of an alkane COH bond by d 8 metal centers (k H /k D Ϸ 2.5-5) (25,26).…”
supporting
confidence: 71%
“…The extensive isotopic scrambling observed for the reaction of 2-d 0.43 with C 6 D 12 , giving CH 2 D 2 and CHD 3 (CD 4 is presumably also formed, but not detected by 1 H NMR) in addition to the CH 3 D, and CH 4 obtained from reactions of all-protio substrates, indicates that reversible steps iii and iv along with COH bond interchange in cyclohexane and methane COH complexes (see below) are all fast relative to loss of methane, consistent with rate-determining COH coordination. This conclusion is further supported by the small KIE [(k H /k D ϭ 1.28(5)], which is similar to values measured for iridium-and rhodium-based COH activation systems where COH coordination is rate-determining (k H /k D Ϸ 1.1-1.4) (22-24), but considerably smaller than values for rate-determining oxidative cleavage of an alkane COH bond by d 8 metal centers (k H /k D Ϸ 2.5-5) (25,26).…”
supporting
confidence: 71%
“…Consequently, this substrate is less effective at producing an oxidative addition product. By using the earlier defined relative rates for coordination, migration, dissociation, and activation for pentane in a kinetic simulation (48), and assuming the same rate constants apply to hexanenitrile, it can be predicted that the preference for pentane over hexanenitrile would be 1.75:1, in good agreement with experiment. Furthermore, because the rates of reductive elimination from both of these activation products is about the same, the kinetic selectivity of 0.27 kcal/mol also corresponds to the thermodynamic selectivity for pentane over hexanenitrile.…”
Section: Discussionmentioning
confidence: 60%
“…Once again, by using the earlier defined relative rates for coordination, migration, dissociation, and activation for alkanes in a kinetic simulation (48), and assuming the same rate constants apply to the alkylnitriles, one can predict the preference for alkylnitrile over acetonitrile. For propionitrile, butyronitrile, and valeronitrile, these simulations give preferences of 1.74:1, 2.02:1, …”
Section: Discussionmentioning
confidence: 99%
“…When compared with a statistical ratio of 6:4:2, this observed ratio corresponds to a thermodynamic preference of 0.13 kcal/mol for CH 2 binding over CH 3 binding. Also, Vetter et al (38) observed a 1.5ϫ kinetic preference for coordination at a secondary COH bond rather than at a primary COH bond for TpЈRhL(alkane) complexes (TpЈϭTris-(3,5-dimethylpyrazolyl) borate; LϭCNCH 2 CMe 3 ).…”
Section: Resultsmentioning
confidence: 99%